Management of Local Own-Source Revenue in Belu Government: A Phenomenological Study - Taek, Filemon Marselinus; Djamhuri, Ali; Baridwan, Zaki (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This study aims to determine the process of managing Regional Original Revenue (PAD) in the Belu Regency government based on the experience of the State Civil Apparatus and to understand and uncover the social meaning that is carried out. The researcher uses the interpretive paradigm understanding method to uncover the intentions and objectives of the informants and uses the Husserl phenomenology approach to explain or uncover the phenomenon of experience based on awareness that occurs by individuals, which in this case is ASN which directly manages PAD. The results of the study revealed that the informants had a lot of experience related to the management of PAD such as non-compliance of taxpayers related to local taxes, the management of regional wealth yields that were separated always exceeded the target and the management of retribution was constrained due to various obstacles. However, the informants interpret the management of PAD as a form of duty and responsibility. Keywords: Government Accounting; Regional Original Revenue; Phenomenology